PENILAIAN POTENSI DAYA TARIK WISATA AIR TERJUN CUCI KAIN DI DESA TEMBAGA KECAMATAN NANGA MAHAP KABUPATEN SEKADAU - Rosita, Theresia; Rifanjani, Slamet (Universitas Tanjungpura, 2018)
Sekadau regency is one of the districts in West Kalimantan province which is known as the small area with triangular transportation potential, There are Nanga Taman and Nanga Mahap area which directly contagious to Ketapang regency. The leading commodities of Sekadau Regency are plantation, agriculture and service sector. On the service sector itself, there are tourisms potentials which have not been known for its existence. Nanga Mahap district is one of them. Kecamatan nangamahap has 12 villages, One of the villages has the potential of tourism that is Cuci Kain Waterfall located in Tembaga village, Nanga Mahap. This study aims to determine the assessment of visitors to the potential tourist attraction and the characteristics of Cuci Kain Waterfall visitors. The research was conducted using survey method with questionnaire / interview technique. Sampling / respondent was done by incidental sampling. The data analysis was done by scoring analysis which is to give an assessment on each element of attraction in Cuci Kain Waterfall guided by ODTWA evaluation guidance PHKA 2003. The result of the research signify the visitors’ assessment on the potential tourist attraction with medium value (B) with value equal to 1,069, 86. Characteristics of the visitors are still dominated by the community around tembaga village, male sex with their last education is senior high school, the age range of 17-26 years been continuing their education as students / college students who have not married yet. Most visitors are coming for recreation, photography and adventure with allowance or monthly income of Rp<1,000,000, - with expenditure of Rp<100.000, - most visitors have > 4 times visits with the duration of visiting <3 hours or 3- 6 hours. Visitors knew the existence of cucikainwaterfall from their friends / family and traveled using two-wheeled vehicles with the number of group >12 people with a difficult terrain to pass.Keywords: Cuci Kain Waterfall, Natural Tourist Attraction And Object, Tourist Attraction, Visitors’ Characteristics